Implementasi Metode Extreme Programming untuk Pengembangan Sistem Online Course pada Madania Centre - Arbi Restandi; Wiga Maulana Baihaqi; Hendra Marcos (Program Studi Teknik Informatika Universitas Pamulang, 2025)
This study implements the Extreme Programming (XP) method for developing an online course system at Madania Centre. The system addresses challenges such as manual transaction processes, inefficiencies, and user unfamiliarity with technology. Using the Laravel framework and Midtrans as a payment gateway, the system streamlines content purchasing and access for users. The research involves stages of planning, design, coding, and testing, ensuring a user-friendly interface and secure transactions. Testing via black-box methodology confirmed the system's reliability. The results demonstrate improved efficiency, better user experience, and operational optimization, making the solution adaptable to similar use cases in educational and consulting sectors.